Pengaruh Audit Internal, Governance Risk Management Compliance Terhadap Fraud Prevention - Yudha Eka Febrian; Akhmad Nofiata (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the effect of internal audit and Governance, Risk Management, and Compliance (GRC) on fraud prevention in State-Owned Enterprises (SOEs) listed on the Indonesia Stock Exchange during the 2021–2023 period. This study employed a quantitative approach using secondary data obtained from companies’ annual reports. The sample was selected using purposive sampling and analyzed through panel data regression. The results show that internal audit has no significant effect on fraud prevention, while Governance, Risk Management, and Compliance (GRC) has a positive and significant effect on fraud prevention. Simultaneously, internal audit and GRC have a significant effect on fraud prevention. These findings indicate that effective GRC implementation plays an important role in improving fraud prevention in State-Owned Enterprises.